2022
DOI: 10.3390/ijerph19031749
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Access to Health Services during the COVID-19 Pandemic: A Scoping Review

Abstract: The COVID-19 pandemic and the measures adopted are having a profound impact on a major goal of public healthcare systems: universal access to health services. The objective is to synthesize the available knowledge on access to health care for non-COVID-19 conditions and to identify knowledge gaps. A scoping review was conducted searching different databases (Medline, Google Scholar, etc.) for original articles published between December 2019 and September 2021. A total of 53 articles were selected and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(112 citation statements)
references
References 133 publications
3
78
1
Order By: Relevance
“…Healthcare utilization and services were dramatically constrained during the COVID-19 pandemic [ 18 , 19 , 20 , 21 ], and it became imperative to protect healthcare workers against infection when caring for COVID-infected patients. In-hospital spread of Omicron infection occurred at our institution in April 2022, after a huge surge of cases in the general population of Taiwan ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare utilization and services were dramatically constrained during the COVID-19 pandemic [ 18 , 19 , 20 , 21 ], and it became imperative to protect healthcare workers against infection when caring for COVID-infected patients. In-hospital spread of Omicron infection occurred at our institution in April 2022, after a huge surge of cases in the general population of Taiwan ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“… 40 The COVID-19 pandemic has greatly affected the provision of care for patients with chronic diseases. 41 So, there is an urgent need to develop innovative ways of caring for patients with chronic diseases during the pandemic. Significant development and integration of digital technology could be the most feasible solution.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies found that 40.9% of adults did not seek proper medical care and 12% opted not to get urgent or emergency care for fear of COVID-19. 5 , 25 Our own patients have expressed concern during the dialysis rounds when angiogram was offered to evaluate the access based on abnormal physical exam finding. Our patients were able to be scheduled for the outpatient procedures including angiograms and thrombectomy if indicated, but it might have taken longer time to schedule because of hesitancy in fear of contracting COVID-19 and due to requirement for a COVID-19 test prior to the procedure.…”
Section: Discussionmentioning
confidence: 99%